Surface deposition of Ag/Ag3VO4 on rod-like BiPO4 to construct plasmon-induced heterostructures with ameliorated photocatalytic performance. (1st June 2021) - Fang, Hongjun; Pan, Yusong; Yan, Haixian; Xu, Linfeng; Pan, Chengling
Abstract: Novel plasmonic photocatalysts have been extensively investigated because of their advantages in efficient light absorption and surface plasmon resonance effect (SPR). Herein, plasmon-induced BiPO4 /Ag/Ag3 VO4 heterostructures were constructed by in-situ partially reduction along with hydrothermal approach. Photo-degradation results revealed that BiPO4 /Ag/Ag3 VO4 -1.2 (abbreviation as Bi/Ag-1.2) product presented a significant enhancement of photoactivity for Methyl orange-MO, Congo red-CR and tetracycline-TC degradation under visible light irradiation, which was higher than that of pristine BiPO4 and Ag/Ag3 VO4, respectively. Moreover, this excellent performance of Bi/Ag-1.2 was mainly ascribed to the synergistic effect consisting of intimate heterostructure between BiPO4 and Ag/Ag3 VO4 and SPR effect of Ag, thus ensuring an accelerated separation and transfer of photo-generated carriers and promoting the absorbance of visible light. The trapping test and electron spin resonance further demonstrated that h + and ·O2 − species are the vital active species in the photocatalytic reaction. Meanwhile, a plausible photocatalytic mechanism induced by plasmon-based heterojunctions was systematically proposed.